Formation of stress students in the process of notions of martial arts in high school - S.V. Uskov (Physical Education of Students)
Various aspects of the development of resistance to psychophysiological stress among students in the classroom arts. In the experiment involved 40 students (20 - boys, 20 girls). In the experiment, teaching methods and means of special psychological training in the martial arts. Disclosed the specifics of individual psycho-oriented methodology in the modern system of martial arts. The possibility of its use in physical education classes. It is noted that not all stress are barriers health, and only excessive. The most destructive are excessive psychogenic stresses caused by adverse of psychological factors. Psychogenic stress has a great destructive impact on health. It is a major cause of morbidity students. Recommended didactically well-designed prevention techniques.